Diversity and Evolution of Viral Pathogen Community in Cave Nectar Bats (Eonycteris spelaea) - Mendenhall, Ian H (Viruses, 2019)
Bats are unique mammals, exhibit distinctive life history traits and have unique immunological approaches to suppression of viral diseases upon infection. High-throughput next-generation sequencing has been used in characterizing the virome of different bat species. The cave nectar bat, Eonycteris spelaea, has a broad geographical range across Southeast Asia, India and southern China, however, little is known about their involvement in virus transmission. Here we investigate the diversity and abundance of viral communities from a colony of Eonycteris spelaea residing in Singapore. Our results detected 47 and 22 different virus families from bat fecal and urine samples, respectively. Among these, we identify a large number of virus families including Adenoviridae, Flaviviridae, Reoviridae, Papillomaviridae, Paramyxoviridae, Parvoviridae, Picornaviridae, and Polyomaviridae. In most cases, viral sequences from Eonycteris spelaea are genetically related to a group of bat viruses from other bat genera (e.g., Eidolon, Miniopterus, Rhinolophus and Rousettus). The results of this study improve our knowledge of the host range, spread and evolution of several important viral pathogens. More significantly, our findings provide a baseline to study the temporal patterns of virus shedding and how they correlate with bat phenological trends.